2010
DOI: 10.1136/aim.2010.003004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ah shi Point Acupuncture on Acne Vulgaris

Abstract: Background Ah shi point acupuncture involves inserting needles at painful or pathological sites. Objective To evaluate the effi cacy of ah shi point and general acupuncture point treatment of acne vulgaris. Methods 36 subjects were recruited and randomised in a double-blind (patient-blind and observer-blind) controlled trial to receive acupuncture either at general acupuncture points only, or at both general acupuncture points and ah shi points 12 times over 6 weeks. The subjects were evaluated using the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
1
20
4
Order By: Relevance
“…After 4-week treatment, the reduction in the number of skin lesions in the acupuncture and sham acupuncture groups was -6.62 ± 15.42 and -15.10 ± 20.13, respectively, with no significant between-group difference (P=0.137). These findings contradict the results of previous trials [11][12][13][14] . On the contrary, after 4-week treatment, the reduction in the Skindex- 16 ; there was a significant between-group difference in this respect (P=0.044).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After 4-week treatment, the reduction in the number of skin lesions in the acupuncture and sham acupuncture groups was -6.62 ± 15.42 and -15.10 ± 20.13, respectively, with no significant between-group difference (P=0.137). These findings contradict the results of previous trials [11][12][13][14] . On the contrary, after 4-week treatment, the reduction in the Skindex- 16 ; there was a significant between-group difference in this respect (P=0.044).…”
Section: Introductioncontrasting
confidence: 99%
“…The demographic and clinical characteristics of the participants at baseline will be recorded by a research assistant: age; gender; race; BMI (kg/m 2 ); marital status; educational level (primary education or below, secondary education, and tertiary education); working duration (<8 hours, [8][9][10][11][12] hours, and >12 hours); duration of sports activities (<7 hours; 7-9 hours; and >9 hours); sleep duration (0-3 times/ month, 1-2 times/week, 3-4 times/week, and ≥ 5 times/week); smoking history; history of alcohol intake; AV duration in months; severity of AV as assessed by global acne grading system (GAGS) score [none (0 score), mild (1-18 score), moderate (19-30 score), severe (31-38 score), and markedly severe (> 39 score)] [25] .…”
Section: Study Recruitmentmentioning
confidence: 99%
“…The difference between the two groups was 8.48±7.74, and there was no significant between-group difference (p = 0.137, > 0.05). These findings contradict the results of previous trials [11][12][13][14] and a systematic review of AV also reported that there is no difference between acupuncture and the waiting list for reducing the number of inflammatory lesions [16] . Unlike drugs, it acts directly on the pathogen, and acupuncture restores normal functions through motivating or inducing the inherent regulatory system in the body and mediating various regulatory systems in the body in order to obtain integral regulation effect [17] .…”
contrasting
confidence: 99%
“…Several trials have indicated that acupuncture may alleviate the skin lesions and improve the QoL of patients with AV [11][12][13][14][15] . However, these trials were affected by potential bias due to the small sample sizes, non-placebo/sham/waiting list control, or use of self-defined outcome measures; thus, these trials did not provide robust evidence of the efficacy of acupuncture in AV patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation